MIXED MODE CATION EXCHANGE CHROMATOGRAPHY LIGANDS BASED ON 1,3-DIOXOISOINDOLIN-2-YL STRUCTURES - LIAO, JIALI; BELISLE, CHRISTOPHER; LOZANO, EDWIN (2024)
The subject invention pertains to proteins are purified by a mixed-mode chromatography system formed by attaching a ligand with cation exchange and hydrophobic 1,3-dioxoisoindolin-2-yl group functionalities to a large-pore support matrix, the only linkage between the ligand and the support matrix being a chain having a backbone of one, two, three, four, or five atoms between the hydrophobic group and the support matrix.